Le Père Lhande, jésuite-reporter de la banlieue - Corinne Bonafoux (Chrétiens et Sociétés, 2015)
In the 1920's, while Paris' suburbs were expanding, a Jesuit, Father Lhande, roamed the "zone", the big housing areas, and wrote sevedressing for several decades: "the social issue and the religious indifference from workers. Father Lhande's books offer both a descrral books with striking headlines: Le Christ dans la banlieue, La Croix sur les Fortifs or Le Dieu qui bouge. The discovery of a new type of urban space, the bareness of the suburbanites and their indifference towards religion was an issue that the Church had been aiption (housing, living conditions, mentality) combining thorough observation and imaginary, and a narrative in which heroes are priests, missionaries in this China-like world right outside of Paris.